Penerapan Prinsip Good Corporate Governance pada Layanan Paketpos (Studi pada Kantor Pos Malang 65100) - Yoga Murlianto (Jurnal Administrasi Publik, 2014)
Abstract: The Principles Implementation of Good Corporate Governance in the Parcell Post Services (Study in the Post Office 65100 Malang). The post office should be able to compete by delivering a quality service to customers. These things need to be done to get the trust of customers.  One of the efforts to improve the company’s performance is by means of applying  the principle of good corporate governance (transparency, accountability, respobility, fairness). The results of the research show that the management of the postal package serveices seen in terms of the process according to the principles of Good Corporate Governance.  In terms of the result can be known that the services provided are good enough, it can be seen from the consumer’s opinion and the sales chart of parcel post service in 2012-2014 that experience increased. However, there are still constraints experienced in the form of human resources was lacking dicipline and facilities and infrastructure. Keywords: good corporate governance, public service.   Abstrak: Penerapan Prinsip Good Corporate Governance pada Layanan Paketpos (Studi pada Kantor Pos Malang 65100). Kantor Pos harus mampu bersaing dengan memberikan pelayanan yang berkualitas kepada pelanggan. Hal tersebut perlu dilakukan untuk  mendapatkan kepercayaan dari pelanggan. Salah satu upaya untuk meningkatkan kinerja suatu perusahaan adalah dengan cara menerapkan Good Corporate Governance (GCG). Hasil dari penilitian menunjukan bahwa pada pengelolaan layanan paketpos dilihat dari segi proses sesuai dengan prinsip Good Corporate Governance (transparansi, akuntabilitas, responbilitas, kewajaran). Sedangkan dari segi hasil dapat diketahui bahwa layanan yang diberikan cukup baik, hal tersebut dapat dilihat dari pendapat konsumen dan grafik penjualan tahun 2012-2014 yang mengalami peningkatan. Namun masih terdapat kendala yang dialami berupa SDM yang kurang disiplin dan sarana dan prasarana.   Kata kunci: good corporate governance, pelayanan publik.